Viability of exogenous stages of development of the causative agent of trichu-riasis of dogs under the influence of temperature - V. Yevstafieva; O. Dolhin (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки, 2022)
Urbanization processes to one degree or another occur in all regions of the planet. Large, small cities and megacities are created, leading to an urban ecosystem with unique abiotic and biotic factors. All this significantly affects the fauna, stability and viability of parasites of domestic dogs, which are representatives of the urban environment. The work aimed to establish the degree of viability of exogenous stages of development of Trichuris vulpis, parasitizing dogs, under the influence of different temperatures. It was established that in laboratory conditions, depending on temperature fluctuations (23 °C–29 °C), the development period of trichurises eggs to the invasive stage ranged from 15 to 27 days. At a 23 °C for 27 days, 74.0 % of invasive T. vulpis eggs were formed. At this temperature, 26.0 % of eggs died during their embryogenesis. At a temperature of 25 °C, the process of egg development to the invasive stage lasted 24 days, where 77.7 % of viable eggs were formed. At this temperature, 22.3 % of trichurises eggs died. As the temperature rises, the egg development period gradually shortens and is 18 days at a temperature of 27 °C, and 15 days at a temperature of 29°C. At the same time, the number of formation of viable invasive eggs decreased and amounted to 81.0 and 64.3 %, respectively, and the percentage of egg death increased to 19.0 and 35.7 %. The terms of formation of various stages of egg development in embryogenesis depended on the temperature, where as its indicators increased, the terms of these stages also shortened. The term of the zygote stage was shortened from 9 to 6 days, the stage of blastomere splitting – from 12 to 6 days, the leguminous embryo stage – from 15 to 6 days, the tadpole embryo stage – from 21 to 9 days, the larval stage – from 24 to 12 days, formation of a mobile larva – from 27 to 15 days. The conducted experimental studies expand the already existing data on the stability of the eggs of trichurises, which parasitize dogs, concerning the influence of temperature in the environment, and also make it possible to correctly establish the terms of preventive measures and prevent the infection of animals through environmental objects.